2013
DOI: 10.1021/am302575p
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Enhancement for Ti-Doped Fe2O3 Thin Film Photoanodes by an In Situ Solid-State Reaction Method

Abstract: In this work, a higher concentration of Ti ions are incorporated into hydrothermally grown Ti-doped (2.2% by atomic ratio) micro-nanostructured hematite films by an in situ solid-state reaction method. The doping concentration is improved from 2.2% to 19.7% after the in situ solid-state reaction. X-ray absorption analysis indicates the substitution of Fe ions by Ti ions, without the generation of Fe²⁺ defects. Photoelectrochemical impedance spectroscopy reveals the dramatic improvement of the electrical conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 43 publications
4
67
0
Order By: Relevance
“…Relatively high C ss value for FZC sample indicates that the multiplied influxes of holes (available for charge transfer to the electrolyte) are driven by the large nanoporous architecture of Fe 2 O 3 photoanode. Higher C ss value is consistent with the cathodic shift in V onset for Fe 2 O 3 films43. In our previous study, it is shown that higher crystalline orientation along (104) plane is consistent with the higher degree of surface states, which resulted in higher C ss value37.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Relatively high C ss value for FZC sample indicates that the multiplied influxes of holes (available for charge transfer to the electrolyte) are driven by the large nanoporous architecture of Fe 2 O 3 photoanode. Higher C ss value is consistent with the cathodic shift in V onset for Fe 2 O 3 films43. In our previous study, it is shown that higher crystalline orientation along (104) plane is consistent with the higher degree of surface states, which resulted in higher C ss value37.…”
Section: Resultssupporting
confidence: 83%
“…Thus, large number of accumulated holes facilitates the water oxidation process leading to early photocurrent onset (as seen from PEC study). Miao et al observed higher C ss value, which is consistent with the cathodic shift in V onset of Fe 2 O 3 films43. Recently, Li et al showed prominent PEC performance for hematite nanorods consisting a thin amorphous TiO 2 layer (as a defect-creating layer) and the improvement is attributed to the accelerated hole-transfer via surface trap at the hematite-electrolyte interface45.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…[85][86][87][88] Lately, Lu et al demonstrated the conductivity and capacitive properties of α-Fe 2 O 3 NRs could be remarkably boosted after introducing oxygen vacancies through a simple and effective method. [85][86][87][88] Lately, Lu et al demonstrated the conductivity and capacitive properties of α-Fe 2 O 3 NRs could be remarkably boosted after introducing oxygen vacancies through a simple and effective method.…”
Section: Fe 2 O 3 -Based Nanostructured Materials For Scsmentioning
confidence: 99%
“…Spins in hematite are slightly canted away from antiferromagnetic (AFM) orientation on the basal plane, giving place to the weakly ferromagnetic (FM) state, between the Morin temperature T M \260 K and the Neel temperature T N \956 K, but the spins are oriented along the [111] axis and perfectly antiferromagnetic below T M [12]. There are a number of reports on the photo-catalytic activity and water splitting properties of a-Fe 2 O 3 nanoparticles by doping suitable dopants [13][14][15][16].…”
mentioning
confidence: 99%